2011
DOI: 10.1017/s0142716411000221
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of compound words in Chinese–English bilingual children: Decomposition and cross-language activation

Abstract: This study investigated compound processing and cross-language activation in a group of Chinese–English bilingual children, and they were divided into four groups based on the language proficiency levels in their two languages. A lexical decision task was designed using compound words in both languages. The compound words in one language contained two free constituent morphemes that mapped onto the desired translations in the other language, such as tooth(牙) brush(刷).Two types of compound words were included: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
3
10
2
Order By: Relevance
“…The two cases of advantage for lexical matching over lexical mismatching among PYPs in the free recall task and the discrete word association task align with our predictions and with Levy, Goral, and Obler's (2007) claim that L2 learners are particularly sensitive to the morphological structure of L1 equivalents. This finding also supports earlier studies (e.g., Cheng, Wang & Perfetti, 2011;Holmquist, 2016;Ko, Wang & Kim, 2011) that showed a facilitatory effect for cases of lexical matching over cases of lexical mismatching. As for Seniors, the finding that two cases of lexical mismatching was recalled better than a case of lexical matching is not in line with our predictions although it could still be used to argue for a continued influence for L1 morphological structure (Levy, Goral & Obler, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The two cases of advantage for lexical matching over lexical mismatching among PYPs in the free recall task and the discrete word association task align with our predictions and with Levy, Goral, and Obler's (2007) claim that L2 learners are particularly sensitive to the morphological structure of L1 equivalents. This finding also supports earlier studies (e.g., Cheng, Wang & Perfetti, 2011;Holmquist, 2016;Ko, Wang & Kim, 2011) that showed a facilitatory effect for cases of lexical matching over cases of lexical mismatching. As for Seniors, the finding that two cases of lexical mismatching was recalled better than a case of lexical matching is not in line with our predictions although it could still be used to argue for a continued influence for L1 morphological structure (Levy, Goral & Obler, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In line with earlier studies (i.e., Cheng, Wang & Perfetti, 2011;Holmquest, 2016;Ko, Wang & Kim, 2011), we predict that L1-L2 lexical mismatching will hinder the processing of L2 words. That is, the L2 words whose morphological structure matches with the structure of their L1 translation equivalents will show a processing advantage over L2 words that exhibit lexical mismatching with their L1 translation equivalents.…”
Section: Research Questionsupporting
confidence: 90%
“…Several findings corroborate with the translation frequency effect in suggesting the presence of a verification process in L2 word recognition. The first one is the translation lexicality effect in L2 compound processing reported by Wang and colleagues (Cheng, Wang, & Perfetti, 2011;Ko, Wang, & Kim, 2011;Wang, Lin, & Gao, 2010). They tested Chinese and Korean ESL speakers on English compound words such as classroom and honeymoon in a LDT.…”
Section: Toward a Verification Model Of L2 Word Recognitionmentioning
confidence: 99%
“…The second question is related to word type, specifically to L2 words without L1 translations. Several studies reviewed earlier already demonstrated that L2 word recognition or production was affected by the extent to which an L2 can be translated into an L1 word (Cheng et al, 2011;Degani et al, 2013;Gollan et al, 2005;Ko et al, 2011). However, little is known about what happens to L2 words that do not have an L1 translation.…”
Section: A Few Issues Associated With Verificationmentioning
confidence: 99%
See 1 more Smart Citation